OPTIMASI KEUNTUNGAN PRODUKSI DENGAN MENGGUNAKAN LINEAR PROGRAMMING - Afnaria Afnaria; Metrilitna br Sembiring; Rina Filia Sari; Syech Suhaimi (MES: Journal of Mathematics Education and Science, 2023)
This research was conducted using data obtained from UD Kreasi Lutvi. Meanwhile, based on the results of production optimization processing using Table Simplex and QM For Windows V3, production levels show different levels of production, namely 80,000 large packages, 5,000 medium packages and 400 small packages. When UD Kreasi Lutvi produces according to optimal conditions, the profit that can be obtained under optimal conditions is Rp. 386,600,000, while the profit in factual conditions is Rp. 361,268,000, so the increase in profits is Rp. 25,332,000. This shows that the benefits in factual conditions and optimal conditions are much different, but to increase profits, UD Kreasi Lutvi must produce according to optimal conditions.